2009
DOI: 10.3182/20090706-3-fr-2004.00106
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive Identification of Volterra Models by Cancellation of the Nonlinear Term

Abstract: We present a new identification method for nonlinear Volterra models of the form HX = F (u, X) + v with H a causal convolution operator. It is based first on a suitable parameterization of H deduced from the so-called diffusive representation, devoted to state representations of integral operators, and second on a suitable operatorial transformation of the problem with the property that the nonlinear term F (u, X) is cancelled, allowing to identify the operator H(∂ t ) alone. Then, the nonlinear term can be id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The application of operator D x;0 to equation (1) leads to the restriction of model (42) to the subsets i;j x;0 , whose interest comes from the following property of operator D x;0 :…”
Section: Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of operator D x;0 to equation (1) leads to the restriction of model (42) to the subsets i;j x;0 , whose interest comes from the following property of operator D x;0 :…”
Section: Proofmentioning
confidence: 99%
“…The identification model considered is the one described in Example 2.4 (and in [30]). For an other concrete example of application, see [42] in which the identification method has been applied to the model of the spherical flame described in Example 2.3. 6.4.1.…”
Section: A Concrete Application Examplementioning
confidence: 99%
“…Second, this method can also be used when the function f changes from one data set to the other. This identification method is still under study: more information about it will be found in (Casenave and Montseny [2009a]). …”
Section: Fig 1 Examples Ofmentioning
confidence: 99%